MENINGKATKAN MOTIVASI BELAJAR SISWA SMP DALAM PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN SCIENTIFIC - Rika Andriany Piliang; Mega Irhamna (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
To generate motivation to learn in mathematics lessons must choose the right method. The method chosen in learning must be a method with a student-centered approach so that students feel more compelled to participate actively in learning. The scientific approach is an approach with basic concepts that accommodate, inspire, strengthen, and underlie thoughts about how learning methods are applied based on certain theories. The set material taught in grades VII-6 of SMP Negeri 2 Deli Tua with a scientific approach is deemed appropriate so that it will be used in this study as a way to increase students' motivation to learn on the set material. The purpose of this study was to increase students' motivation in learning mathematics through a scientific approach in class VII-6 of SMP Negeri 2 Deli Tua for the 2019/2020 academic year. The results of the study show that the scientific approach can increase students' learning motivation on the set material. Data on learning outcomes in cycle 1 is 72.5% of students who complete learning and in cycle 2 it increases to 85%. It can be concluded that the use of the scientific approach in increasing student learning motivation in group learning in grades VII-6 of SMP Negeri 2 Deli Tua for the 2019/2020 academic year is right on target.